Sing4Health: protocol of a randomized controlled trial of the effects of a singing group intervention on the well-being, cognitive function and health of older adults - Galinha, Iolanda Costa (2020)
Singing is a multimodal activity that requires physical, cognitive and psychosocial performance, with benefits to various domains of well-being and health in older adults. In recent years, research has increasingly studied group singing as an important cost-effective intervention to promote active and healthy aging. However, the specific factors responsible for these benefits need further experimental support, as most studies do not allow for causal inferences. This study responds to the need for further randomized controlled trials (RCT), with follow-up measurement, on the benefits of group singing in older adults from a low socioeconomic background. Also, while most studies often focus on specific outcome measure dimensions, in this study, the conjoint effect of several physical, psychosocial, psychoemotional and cognitive dimensions are analyzed, testing mediation effects of psychosocial and psychoemotional variables on the well-being and health of the participants.